Vertical-torsional oscillations and dissociated bilateral horizontal gaze palsy in a patient with a pontine cavernous angioma. Issue 2 (14th January 2005) - Washio, N; Suzuki, Y; Yamaki, T; Kase, M; Ohtsuka, K
Abstract : We report the case of a 16 year old girl with vertical-torsional oscillations. She had a 4 year history of bilateral horizontal gaze palsy caused by a cavernous angioma in the medial part of the dorsal pons. She presented with vertical oscillopsia that had worsened during the past 3 months. Unilateral three dimensional eye movements and bilateral horizontal eye movements were recorded using a magnetic search coil method and direct current electro-oculography, respectively. She had vertical-torsional oscillations (average frequency: 3.0 Hz) leaving vertical saccades and pursuits intact. The average amplitudes of the vertical and torsional components were 2.0° and 0.6°, respectively. Her horizontal rapid eye movements were severely impaired; however, her horizontal pursuits and slow phases of vestibulo-ocular reflex were only partially impaired (gain<0.3, oculomotor range<±9°). Convergence and divergence were intact. Lesions involving the medial part of the dorsal pons and bilateral paramedian pontine reticular formation can induce vertical and torsional oscillations without disruption of vertical rapid eye movements.